Comparative 2d And 3d Ultrasonographic Imaging Of Developmental Changes Of Urinary Bladder In Dogs - Kumar, Dinesh; Behl, S.M.; Singh, Prem; Tayal, Rishi; Pal, Madan; Saharan, Sandeep; Chandolia, R.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was undertaken in six apparently healthy pups of mixed mongrel breed from the same litter irrespective of their sex. Normal ultrasonographic images of development of urinary bladder were obtained by 2D and 3D ultrasonography. First scanning was done on the 15th day of age and at 15 days interval till the two month of age and then at the interval of one month till eight month of age.The wall thickness, diameter, length and circumference of urinary bladder were measured. There was linear increase observed in the bladder parameters with age. The change in parameters was also dependent on the fullness of the urinary bladder. At 15th day the urinary bladder appeared as a small anechoic structure with indistinct wall. With advancement of age the size and capacity of urinary bladder increases. The circumference of the bladder was found maximum at 240th day of age.
Keywords: Ultrasonography; Hypoechoic; Hyperechoic; Anechoic